STUDI PERKIRAAN SUSUT ENERGI DAN DAYA LISTRIK PADA JARINGAN TRANSMISI TEGANGAN TINGGI 150 KV JAJAR - MANGKUNEGARAN Studi Kasus Pada PT. PLN (Persero) APP SALATIGA - De Arsilla, Alfian (2017)
Electricity is a vital requirement for human life. PT. PLN (Persero) is always trying to provide power supply with the reliability and quality of electricity the best, at the time of the distribution process of the plant to the consumer needs to be a power line including the transmission line. The distribution process will experience power losses in both the conductor and transformer. This analysis aimed to determine and compare the value between manual calculation with the simulation results of ETAP 12.6. This analysis was conducted to determine the value of power loss of the transmission line Jajar to Mangkunegaran. The method used starting from the collection of data in GI Jajar-Mangkunegaran, calculations manually, create a single line diagram in ETAP 12.6, perform simulations and compare the simulation results with manual calculations, then it can be deduced. Data were collected during the month at 10:00 and 19:00. The transmission line is wearing a conductor with XLPE type with a diameter of 240 mm². The results of this study, the power losses during the month amounted to 16209.552 kWh at a cost of Rp.19.282.059,00 loss. The most substantial power losses occur at noon on 7 November amounted to 0.0288660 MW and the smallest loss during the night of 0.0158807 MW. Loss on transformer for one month at a time during the day amounted to 607,715 kW, while in the evening of 575 kW.